Body surface scan anthropometrics are associated with grip strength in the general population - Filges, Berit; Bahls, Martin; Radke, Dörte; Groß, Stefan; Ewert, Ralf; Stubbe, Beate; Markus, Marcello RP; Felix, Stephan B.; Völzke, Henry; Dörr, Marcus; Köhler, Armin; Ittermann, Till (Nutrition, metabolism, and cardiovascular diseases, 2024)
Body shape and anthropometrics are well-known risk factors for cardiovascular diseases (CVD) and mortality. Hand-grip strength (HGS) is also a meaningful marker of health and a promising predictor of CVD and mortality. There is a lack of studies that have systematically investigated associations between body shape and anthropometrics with HGS. In a population-based study, we investigated if anthropometric markers derived from 3D body scanning are related to HGS. We used the data of 1,599 individuals aged 36 to 93 years, who participated in the Study of Health in Pomerania. A total of 87 anthropometric markers, determined by a 3D body scanner, were included in the analysis. Anthropometric measurements were standardized and used as exposure variables. HGS was measured with a hand dynamometer and used as outcome. Sex-stratified linear regression models adjusted for age and height were used to relate standardized anthropometrics and HGS. Anthropometric markers were ranked according to -log-p-values. In men, left and right forearm circumference, left arm length to neck (C7), left forearm length, and forearm-fingertip length were most strongly related to HGS. In women, right forearm circumference, forearm-fingertip length, shoulder breadth, left forearm circumference, and right wrist circumference showed the most significant associations with HGS. The final prediction models contained 13 anthropometric markers in males (R2=0.54) and eight anthropometric markers in females (R2=0.37). The identified parameters may help estimate HGS in the clinical setting. However, studies in clinical settings are essential to validating our findings. •In both sexes, forearm circumference and forearm-fingertip length showed the strongest associations with handgrip strength.•The identified body shape measures may be useful monitoring markers in the clinical setting.•Prediction models were generated, showing another potential value of the identified anthropometric markers in clinical practice.